Wakaf: Perannya Dalam Peningkatan Ekonomi Umat - Erizal Erizal (TERAJU: Jurnal Syariah dan Hukum, 2020)
Representation or endowment is an institution in an established Islamic religion. In Islamic law, this waqf is included in the category of community worship (Ijtimaiyah worship). Throughout Islamic history, waqf is a very important means and capital in advancing the development of religion. In fact waqf is one of the Islamic institutions which has the potential to be further developed to help disadvantaged people. Unfortunately there are so many endowments, in general their use is still traditional consumptive and not professionally managed professionally.